THE UTILIZATION OF MIND MAPS TO ASSIST A STUDENT WITH AUTISM SPECTRUM DISORDER: Received: 29th October 2021; Revised: 10th January 2022, 05th March 2022; Accepted: 06th March 2022 - Winardi, Andreas (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Everybody has the right to get an education; a student with autism spectrum disorder (ASD) is no exception. The researcher had an ASD student in his Curriculum and Material Development class. It turned out that the student struggled to comprehend and memorize the materials. Therefore, the researcher decided to use mind maps to assist him. Action research was conducted to investigate the challenges and benefits of using mind maps. The research employed three gathering techniques namely, observations, content analysis, and an interview. The findings suggest that the ASD student often forgot how to make an effective mind map and he found it difficult to make a mind map without getting any help. Hence, repetitions and assistance from lecturers in making mind maps are of utmost importance. With the help of the lecturers, the ASD student found it easier to comprehend and memorize the materials.